Lymphatic drainage of lung cancer follows an intersegmental pathway within the visceral pleura. (April 2021) - Fourdrain, Alex; Epailly, Julien; Blanchard, Chloé; Georges, Olivier; Meynier, Jonathan; Berna, Pascal
Highlights: Lung cancers are known to be highly lymphophilic tumors. Lymphatic drainage of the lung follows both a peribronchial and a visceral pleura pathway. Lymphatic drainage of lung cancer in the visceral pleura largely follows an intersegmental pathway. Peripheral location of the tumor is a risk factor for intersegmental visceral pleura lymphatic drainage. Abstract: Objectives: Lung cancer tumors are known to be highly lymphophilic. There are two different pattern of lymphatic drainage of the lung: one peribronchial lymphatic pathway, and another one within the visceral pleura which appears to be more intersegmental than the peribronchial pathway. We aimed to assess the prevalence of an intersegmental pathway in the lymphatic drainage of lung tumors within the visceral pleura and determine potential influential factors. Methods: In this prospective study, we included all patients for whom a major pulmonary resection (lobar) was indicated and performed for suspected or proven lung cancer. An immediate ex-vivo evaluation of the surgical specimen after resection was conducted by trans-pleural injection of blue dye within the tumor. The pathways followed by the lymphatic vessels under the visceral pleura were assessed to define the occurrence of an intersegmental pathway, which was defined by the presence of blue dye within the lymphatic vessel crossing to a neighboring pulmonary segment, distinct from the tumorous segment. Results: Fifty-three patients met the inclusion criteria and were assessed over a three-year period. Lymphatic drainage within the visceral pleura followed an intersegmental pathway in 35 of 53 patients (66 %). When the lymphatic drainage of the tumor was intersegmental, it drained in a single other segment in 21/35 cases and two or more in 14/35 cases. Logistic regression with multivariate analysis showed a peripheral location of the tumor to be a risk factor for the intersegmental pathway of visceral pleura lymphatic drainage (OR = 0.87 [079−0.95], p = 0.003). Conclusion: These results confirm that lymphatic drainage of lung cancer in the visceral pleura appears to largely follow an intersegmental pathway, especially when the tumor is peripheral, close to the visceral pleura.